Analysis of Sales System Implementation in Primary Cooperative Tribuana II - Tino Feri Efendi; Muhammad Sidiq (International Journal of Computer and Information System (IJCIS), 2020)
Primer KoperasiTribuana II is a business entity (cooperative) under the auspices of Group 2 Kopassus, Kartasura, Sukoharjo. This cooperative was established to meet the needs of members, both from an economic, social and cultural perspective. Primer KoperasiTribuana II was founded on September 14, 1968 under the name Primkopad H-09. This cooperative has changed its name several times, and the last name uses the Primary KoperasiTribuana II. In an effort to meet the needs of the members, the Tribuana II Primary Cooperative carries out several activities, including savings and loans and sales of daily necessities (shops). In fulfilling the needs, especially for stores, the Tribuana II Primary Cooperative sells goods which in its activities are still using the old method (manual). This is considered very ineffective and efficient and can not increase sales profit in a relatively fast time. For that we need a system that can help smooth the sale of goods. In solving this problem, the authors designed a sales information system. In this design, the author uses the Visual FoxPro programming language. The method in this research is waterfal method. The method in this research is through interviews, observation and literature study. The system design is made with context diagrams, HIPO, input output design and Data Flow Design. The system is created in a program with the Visual FoxPro programming language with a database format using MySQL. The result of this design is to produce an application program that will be used for the web-based sales process at the Tribuana II Primary Cooperative and it is hoped that it will facilitate daily transaction activities and compile reports to be faster and more efficient.